2023
DOI: 10.1186/s12879-023-08574-5
|View full text |Cite
|
Sign up to set email alerts
|

Leptospirosis in humans and selected animals in Sub-Saharan Africa, 2014–2022: a systematic review and meta-analysis

Jacob Mugoya Gizamba,
Lawrence Mugisha

Abstract: Background Leptospirosis is an emerging neglected tropical zoonotic disease of public health importance causing substantial morbidities and mortalities among humans. The infection is maintained within the population through interactions between humans, animals, and the environment. Understanding the burden of disease in both humans and animals is necessary for effective prevention and control in Sub-Saharan Africa (SSA). Therefore, we aimed to determine the seroprevalence of leptospirosis in hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 63 publications
0
3
1
Order By: Relevance
“…Baseline screening of PWH in our study revealed HTN prevalence of 37.2%. Our finding was higher than the 17% reported in Nigeria [ 9 ] and 27% from a meta-analysis from South Africa [ 11 ], but was lower than the prevalence of 43% reported in Tanzania [ 10 ]. The higher prevalence from our study compared to the one from Nigeria may be due to our patients being mostly ART experienced compared to ART-naive patients from the Nigerian study as ART has been linked to development of CVDs [ 19–21 ].…”
Section: Discussioncontrasting
confidence: 92%
See 1 more Smart Citation
“…Baseline screening of PWH in our study revealed HTN prevalence of 37.2%. Our finding was higher than the 17% reported in Nigeria [ 9 ] and 27% from a meta-analysis from South Africa [ 11 ], but was lower than the prevalence of 43% reported in Tanzania [ 10 ]. The higher prevalence from our study compared to the one from Nigeria may be due to our patients being mostly ART experienced compared to ART-naive patients from the Nigerian study as ART has been linked to development of CVDs [ 19–21 ].…”
Section: Discussioncontrasting
confidence: 92%
“…HTN prevalence in PWH in SSA has varied widely in literature, with crude prevalence of 17% among ART-naive PWH in Nigeria [ 9 ] to 43% in PWH on ART in Tanzania [ 10 ]. A meta-analysis from South Africa also reported a prevalence of 25.5% among 123 951 PWH from 22 studies [ 11 ]. The prevalence of HTN, both in the general population and among PWH, is likely to be underrated in SSA due to complex factors such as diverse diagnostic criteria, poor surveillance, poor health-seeking behavior, and inadequate resources for screening for HTN, among others [ 11–13 ].…”
mentioning
confidence: 99%
“…On the other hand, almost half of our cohort had GWG above the NAM recommended range, including one-third of WHIV. These results are concerning considering that PHIV already have a higher risk of adverse birth outcomes [37,38] and metabolic health outcomes associated with HIV-induced chronic inflammation [39][40][41]. In addition, unwanted GWG in PHIV could exacerbate their poor mental health and negatively affect ART adherence [42].…”
Section: Discussionmentioning
confidence: 99%
“…A diverse array of domestic and wild animals likely serve as reservoirs by excreting Leptospira in their urine [14][15][16]. Rats are thought to be important in transmission of Leptospira to humans, however in some settings, prevalence is higher in livestock suggesting that other animals also play significant roles [16][17][18][19][20][21][22][23]. Unfortunately reports of seroprevalence in wild animals are scarce [24][25][26][27][28][29][30][31], leaving gaps in our understanding of how interactions between domestic animals and wildlife influence prevalence in domestic animals and ultimately, transmission to humans.…”
Section: Introductionmentioning
confidence: 99%